Utilizing Charts as Visual Media to Improve Student Understanding - Suci Ramadhani (CV Grasta Glory, 2026)
Learning media are tools used by educators to convey information to students so that they can understand it well. With advances in information technology, learning media has evolved from solely print to include a wider range of visual and multimedia media. Using these diverse media can help students access information in different ways and increase their motivation and engagement in learning. Charts are one visual medium that can be used effectively. Media that relies on sight, such as images, graphs, tables and charts, is called visual media. Charts are useful for presenting information in a systematic, concise, and easy-to-understand way, helping students see the relationships between concepts more clearly. This is very relevant for learning in elementary schools because it can simplify complex material and make learning more interesting. The discussion results indicate that charts are crucial for enhancing student understanding, helping them organize information, and encouraging them to actively participate in the learning process. However, charts have several drawbacks: they are time-consuming to create, and not all materials are suitable for this format. Therefore, teachers must use charts appropriately to ensure effective learning.